Exploiting Marine BD to Develop MLDB and Its Application to Ship Basic Planning Support - Mohammad Danil Arifin; Fanny Octaviani (Institut Teknologi Sepuluh Nopember, 2021)
Recently, the global marine logistics industry has changed significantly because of the global movement of goods. Where the amount of available data and attention paid to extensive data analysis in various topics exponentially grows, it is possible to obtain vast amounts of marine BD. However, the collection of BD groups is difficult to organize and frequently redundant. This is why the database can be so important. If these BD are effectively utilized, great innovation can be achieved in the marine industry. In this study, we develop a marine logistics database to ship basic planning support in the future. The database under study consists of BD sets, i.e. port, ship, route, international trade, and ship operation information from automatic identification system data. As a result, the relational database was developed. The effectiveness of the database is evaluated and extracted data from the database necessary for ship basic planning is discussed.